2021
DOI: 10.1371/journal.pone.0254352
|View full text |Cite
|
Sign up to set email alerts
|

Maintaining oxygen delivery is crucial to prevent intestinal ischemia in critical ill patients

Abstract: Background Intestinal ischemia is a common complication with obscure pathophysiology in critically ill patients. Since insufficient delivery of oxygen is discussed, we investigated the influence of oxygen delivery, hemoglobin, arterial oxygen saturation, cardiac index and the systemic vascular resistance index on the development of intestinal ischemia. Furthermore, we evaluated the predictive power of elevated lactate levels for the diagnosis of intestinal ischemia. Methods In a retrospective case-control st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 67 publications
0
2
0
Order By: Relevance
“…A key component of ECMO treatment is to increase or preserve DO 2 [ 6 , 22 ]. The safe threshold of DO 2 for the individual patient is unknown, but a range between 400 and 600 ml/min/m 2 is probably reasonable [ 23 , 24 ] in critical ill patients. Therefore, both ventilation strategies appear to be viable in patients treated with ECMO.…”
Section: Discussionmentioning
confidence: 99%
“…A key component of ECMO treatment is to increase or preserve DO 2 [ 6 , 22 ]. The safe threshold of DO 2 for the individual patient is unknown, but a range between 400 and 600 ml/min/m 2 is probably reasonable [ 23 , 24 ] in critical ill patients. Therefore, both ventilation strategies appear to be viable in patients treated with ECMO.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, multiple studies showed that blood lactate levels relate to mortality in patients treated in the ICU, independently from the underlying critical illness [ 8 , 9 , 11 , 12 , 13 ]. However, the predictive power of a single lactate value is limited [ 14 , 15 , 16 ], and consecutive studies have revealed that serial evaluations of lactate and derived values strengthen the predictive value regarding mortality [ 17 , 18 , 19 ]. In this context, a calculated parameter incorporating the sum of the areas under the curve (AUCs) of serial lactate levels was introduced to capture the severity and duration of hyperlactatemia [ 19 , 20 , 21 , 22 , 23 , 24 , 25 ], which is normalized in most studies for the observed time interval [ 20 , 21 , 23 , 24 , 25 ].…”
Section: Introductionmentioning
confidence: 99%